PUM1 Is Overexpressed in Colon Cancer Cells With Acquired Resistance to Cetuximab - Liu, Qizhi; Xin, Cheng; Chen, Yikuan; Yang, Jiawen; Chen, Yingying; Zhang, Wei; Ye, Lechi (Frontiers in Cell and Developmental Biology, 2021)
Background: Cetuximab is an effective antibody to treat colorectal cancer (CRC) by targeting the epidermal growth factor receptor (EGFR). However, the mechanisms of acquired resistance to cetuximab therapy, especially in patients without identifiable gene mutations, are not fully understood. Methods: Our study investigated the role of pumilio RNA binding family member 1 (PUM1) in cetuximab resistance. We established cetuximab-resistant colon cancer cell lines SW480R and Caco-2R, and knocked out PUM1 and DEAD-box helicase 5 (DDX5) with CRISPR/Cas 9 system. To check the cell proliferation, we used cell counting kit-8. We performed qPCR and immunoblot to examine the levels of mRNAs and proteins for each cell line. Results: Our data showed PUM1 was up-regulated in SW480R and Caco-2R cells with increased protein levels and cell proliferation, and PUM1 knockout reduced the cell viability in presence of cetuximab. We also found that PUM1 interacted with DDX5 in 3’ UTR as well as positively regulated its mRNA expression. Furthermore, suppression of DDX5 also decreased the proliferation of SW480R and Caco-2R cells. Conclusion: Our study suggests that PUM1 positively regulates DDX5 and acts as a promoter in cetuximab resistant colon cancer cells.